2021
DOI: 10.3390/en14092491
|View full text |Cite
|
Sign up to set email alerts
|

Anaerobic Co-Digestion of Tannery and Slaughterhouse Wastewater for Solids Reduction and Resource Recovery: Effect of Sulfate Concentration and Inoculum to Substrate Ratio

Abstract: Anaerobic digestion is considered unsuitable for the bioremediation of tannery effluent due to process inhibition, mainly due to high concentrations of sulfur species, and the accumulation of H2S and/or NH3. This study using the standardized biochemical methane potential protocol showed that efficient processing is possible with slaughterhouse wastewater, provided sufficient functional biomass is present at the start of the process and the SO42− concentration is below inhibition threshold. Methanogenic activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…The results of the theoretical methane yield based on the elemental composition according to each OLR indicated that the theoretical methane yield increased owing to the increasing carbon content as the OLR increased [34]. A previous study improved the methane yield by adding carbon to the AD reactor [35]. The researchers reported that methane yield was improved as the carbon addition increased within an optimal OLR range [35].…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…The results of the theoretical methane yield based on the elemental composition according to each OLR indicated that the theoretical methane yield increased owing to the increasing carbon content as the OLR increased [34]. A previous study improved the methane yield by adding carbon to the AD reactor [35]. The researchers reported that methane yield was improved as the carbon addition increased within an optimal OLR range [35].…”
Section: Discussionmentioning
confidence: 98%
“…A previous study improved the methane yield by adding carbon to the AD reactor [35]. The researchers reported that methane yield was improved as the carbon addition increased within an optimal OLR range [35]. It was concluded that food waste can produce more methane than other substrates because of its high carbon content.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The characteristics of the TWW are given in Table 1. All analytical procedures were performed as previously described [18].…”
Section: Tannery Wastewatermentioning
confidence: 99%